The Effect Of Organizational Commitment And Work Competency On Employee Performance At The Morowali Regent's Office - Megar; Andi Indriani Ibrahim; Yobert Kornelius; Riswandi Palawa (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of organizational commitment and work competence on employee performance at the Morowali Regent's Office. This study uses a quantitative approach with an associative research design. The study population was all civil servants working at the General Section of the Morowali Regent's Office, with a census sampling technique, resulting in 109 respondents. Data were collected through a closed-ended questionnaire using a five-point Likert scale arranged based on indicators of organizational commitment, work competence, and employee performance. Data analysis was conducted using multiple linear regression with the help of SPSS version 25 software, through stages of validity testing, reliability, classical assumption testing, and partial and simultaneous hypothesis testing. The results of the study indicate that organizational commitment has a positive and significant effect on employee performance, as well as work competence which is proven to have a positive and significant effect on employee performance. Simultaneously, organizational commitment and work competence have a significant effect on employee performance. This finding indicates that improving civil servant performance is not only determined by technical abilities, but also by psychological attachment and employee loyalty to the organization. The implications of this study emphasize the importance of strengthening organizational commitment and developing work competence through continuous training as a basis for formulating human resource management policies in the local government environment.